The Shamrock and the Cross : Irish American Novelists Shape American Catholicism. - Sullivan, Eileen P. (University of Notre Dame Press, 2016)
"In The Shamrock and the Cross: Irish American Novelists Shape American Catholicism, Eileen P. Sullivan traces changes in nineteenth-century American Catholic culture through a study of Catholic popular literature. Analyzing more than thirty novels spanning the period from the 1830s to the 1870s, Sullivan elucidates the ways in which Irish immigration, which transformed the American Catholic population and its institutions, also changed what it meant to be a Catholic in America. In the 1830s and 1840s, most Catholic fiction was written by American-born converts from Protestant denominations; after 1850, most was written by Irish immigrants or their children, who created characters and plots that mirrored immigrants' lives. The post-1850 novelists portrayed Catholics as a community of people bound together by shared ethnicity, ritual, and loyalty to their priests rather than by shared theological or moral beliefs. Their novels focused on poor and working-class characters; the reasons they left their homeland; how they fared in the American job market; and where they stood on issues such as slavery, abolition, and women's rights. In developing their plots, these later novelists took positions on capitalism and on race and gender, providing the first alternative to the reigning domestic ideal of women. Far more conscious of American anti-Catholicism than the earlier Catholic novelists, they stressed the dangers of assimilation and the importance of separate institutions supporting a separate culture. Given the influence of the Irish in church institutions, the type of Catholicism they favored became the gold standard for all American Catholics, shaping their consciousness until well into the next century"--